A summons to memphis eaudiobook - Taylor, Peter (Recorded Books Inc., 2013)
Born in 1917, Tennessee author Peter Taylor won the Pulitzer Prize for this exceptional work of literature. The New York Times Book Review calls this "a beautiful ironic novel," and Kirkus Reviews hails it as "every inch the classic." The well-to-do Carver family moves to Memphis from Nashville, where they become embroiled in a domestic dispute over the widower patriarch's decision to remarry.